Clinical usefulness of a rapid molecular assay, ID NOW™ influenza A & B 2, in adults. Issue 3 (March 2021) - Mitamura, Keiko; Yamazaki, Masahiko; Ichikawa, Masataka; Yasumi, Yuki; Shiozaki, Ken; Tokushima, Masahiko; Abe, Takashi; Kawakami, Chiharu
Abstract: Introduction: ID NOW™ Influenza A & B 2 (ID NOW 2) is a rapid molecular assay that combines two characteristics, namely the rapidness of rapid antigen detection test (RADT) and the high sensitivity of molecular assay. Methods: The clinical performance of ID NOW 2 compared with real-time RT-PCR was evaluated in adults. Results: The sensitivity of ID NOW 2 over multiple seasons from 2016/2017 to 2019/2020 was 97.3% (95% CI: 90.7–99.7) for Type A, 100% (95% CI: 81.9–100) for Type B, and 97.8% (95% CI: 92.2–99.7) for influenza (Type A + Type B), and it was significantly higher than the sensitivity of RADT, which was 80.0% (95% CI: 69.2–88.4) for Type A, 73.3% (95% CI: 44.9–92.2) for Type B, and 78.9% (95% CI: 69.0–86.8) for influenza. The sensitivity of RADT tended to be lower in patients in the particularly early period, within 12 h from disease onset; however, the sensitivity of ID NOW 2 remained high, increasing the difference between the sensitivity of RADT and ID NOW 2. The viral loads were low within 12 h from onset, and it was considered this affected the sensitivity of RADT due to its low analytical sensitivity. The specificity of ID NOW 2 was 98% or greater in all groups. Conclusions: Since ID NOW 2 has a high sensitivity and specificity in adults, it is anticipated to be used in clinical practice, particularly in patients who require early and accurate diagnosis.